2022
DOI: 10.3390/healthcare10030459
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Self-Sampling Devices for Molecular Detection of Human Papillomavirus (HPV) and Other Sexually Transmitted Infections (STIs): A Pilot Study

Abstract: Background: Cervical cancer is the fourth most common cancer in women, and it is well known that high-risk human papillomavirus (hrHPV) infections are the necessary carcinogenic factors for the development of cervical tumors. Moreover, the interaction between HPV and other sexually transmitted infections (STIs) may increase the risk of cancer progression. Self-sampling has been demonstrated to represent a valid and well-accepted alternative, favoring women’s participation in screening programs. This study aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…Nowadays, several devices for self-sampling are commercially available, with different performances in sample collection [ 24 , 25 , 26 ]. The majority of HPV molecular assays are validated on cervical samples, the gold standard in cervical cancer screening [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, several devices for self-sampling are commercially available, with different performances in sample collection [ 24 , 25 , 26 ]. The majority of HPV molecular assays are validated on cervical samples, the gold standard in cervical cancer screening [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the implementation and utilization of the HerSwab sampling test will be successful in increasing CCS patronage, early detection of CC lesions, and reducing mortalities associated with CC. 37,45,46 For instance, a study conducted among women in New Zealand on HPV self-sampling acceptability reported that 78% indicated a preference for self-sample, compared to 22% who preferred a physician-collected sample. 29 Furthermore, research done in Canada among under-screened women from Rural Ontario discovered that women who received HPV self-sampling kits were 3.7 times more likely to screen than Physician collected samples.…”
Section: Evaluation Of Herswab Hpv Self-sampling Techniquementioning
confidence: 99%
“…49 It was also suggested the need to evaluate newly developed vaginal self-screening devices to increase their accessibility by women and also to identify and solve barriers that may hinder their implementation. 46 More randomized control trial studies are therefore needed across various countries to evaluate the effectiveness, acceptability, and anticipated and unanticipated challenges of implementing HerSwab tests nationwide. This new technology should be evaluated in less advanced countries such as those in Sub-Saharan Africa (SSA) to detect how well it could be introduced and well implemented in these countries.…”
Section: Evaluation Of Herswab Hpv Self-sampling Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Improving the participation of non-attenders in CC screening programmes should be a public health priority. HPV self-sampling method proved to have a good acceptability of HPV testing, and positive attitudes towards HPV diagnostic procedures by the women, and good concordance in the detection of carcinogenic HPVs compared with cervical samples 11–13. Also, several studies have shown that offering self-sampling can lead to increased participation rates in CC screening and has been implemented already in many countries (eg, the Netherlands, Australia, Finland) 14.…”
Section: Introductionmentioning
confidence: 99%